2002
DOI: 10.1007/s00125-002-0782-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular targets of redox signalling in diabetes mellitus

Abstract: There is overwhelming evidence for an involvement of reactive oxygen species (ROS) in the pathogenesis of diabetes-associated vascular complications. However, neither the exact source of the ROS initiating cascades leading to cell dysfunction in diabetes nor their chemical nature is fully understood. Furthermore, despite our knowledge of the crucial role of ROS in diabetes, little is known about the actual targets and the molecular consequences of the interaction of ROS with cellular signalling pathways.Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 99 publications
1
93
1
3
Order By: Relevance
“…Moreover, D-glucose-dependent · O 2 -release from porcine aortic SMC is in line with our previous report that the release of · O 2 -is enhanced in uterine arteries of diabetic patients [6]. The source of SMC · O 2 -and the mechanisms of its release under elevated D-glucose conditions are still a matter of debate, but NAD(P)H oxidase [29,30,31,32,33] and mitochondria [34,35] have been discussed frequently to contribute to increased · O 2 -production in diabetes [7]. Overall, recent literature and our present data suggest that under hyperglycaemic conditions · O 2 -release from SMC is augmented and affects EC function.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, D-glucose-dependent · O 2 -release from porcine aortic SMC is in line with our previous report that the release of · O 2 -is enhanced in uterine arteries of diabetic patients [6]. The source of SMC · O 2 -and the mechanisms of its release under elevated D-glucose conditions are still a matter of debate, but NAD(P)H oxidase [29,30,31,32,33] and mitochondria [34,35] have been discussed frequently to contribute to increased · O 2 -production in diabetes [7]. Overall, recent literature and our present data suggest that under hyperglycaemic conditions · O 2 -release from SMC is augmented and affects EC function.…”
Section: Discussionsupporting
confidence: 89%
“…Although these data might be related to this particular type of artery and are in contradiction with reports in murine models [7], it is unclear whether, and if so, how vascular SMC affect EC during diabetes. Such smooth muscle originated modulation of EC function adds to our recent paradigm in which vascular dysfunction in diabetes (and many other diseases) is thought to occur initially in EC that, in turn, affects the vascular SMC [1,8].…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…14 Prolonged hyperglycemia induces increased levels of ROS such as hydrogen peroxide, hydroxyl radicals and super oxide anions. 19,20 Hyperglycemia and ROS have also been correlated with an elevation of MMP-9 expression and activity that can be attenuated by treatment with antioxidants. 17 It is apparent that in the development of diabetes proteinase expression may be increased by a variety of biochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS production increases within hours in many instances, such as inflammation, and it significantly increases the amount of NO [47,48]. Likewise, it was also shown that high glucose levels significantly increased iNOS activity [49,50]. Additionally, diabetes induced increasing iNOS activity which damaged cellular proteins, inhibited the lipid and protein functions in the neurons and also dis- rupted haemostasis [51].…”
Section: Discussionmentioning
confidence: 98%